Effects of sheep diet on nutrient cycling in mixed farming systems of semi-arid West Africa - Powell, J.M.; Fernández Rivera, S.; Hofs, S. (Elsevier, 1994)
The cycling of biomass through livestock into manure and urine that fertilise the soil is an important linkage between livestock and soil productivity in semi-arid West Africa. This study was conducted to determine the effects of different forage leaves on the amounts and forms of nutrients excreted by sheep, the relationship between diet quality and nutrient voidings, and to evaluate the potential impact of these effects on the release of nutrients from urine and faeces when used as organic fertilisers. Five diets consisting of Pennisetum glaucum (PG), Vigna unguiculata (VU), Acacia trachycarpa (AT), Guiera senegalensis (GS) and Combretum glutinosum leaves were fed to growing sheep. The total amount and proportion of nutrients voided in faeces and urine was highly influenced by the N and P contents of the feeds, and the lignin: neutral detergent fibre, lignin:N, and polyphenol:N ratios. Sheep fed VU leaves excreted significantly more total-N than sheep fed any of the browse leaves. Feeding browse caused a general shift from faecal-soluble N (microbial and endogenous N) to faecal-insoluble N (undigested plant N). Animals fed VU leaves voided large amounts of urine N which would be susceptible to large volatilisation losses. Sheep fed browse leaves voided less urine N, and therefore produced excreta less susceptible to volatile-N losses. The estimated 45–54 kg N and 5.1–7.8 kg P ha−1 released from the various faeces would provide an important contribution to the annual requirements of millet of 36 kg N and 6.1 kg P ha−1. Selecting feeds that not only satisfy the nutrient requirements of livestock but produce animal excreta less susceptible to losses may improve nutrient cycling in mixed farming systems of semi-arid West Africa.